Enhancing Reporting Skills of Grade 12 ABM Students to Improve their Performance Tasks (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
This study is all about enhancing the reporting skills of Grade 12 Accounting, Business, and Management Strand students. Reporting a topic is one way of participating in class but mastering the topics, overcoming their fears, and lacking self-confidence are the main problems of some students when they are reporting. Presenting in front of other people may be difficult because of the said factors. The researchers used the survey method because this is the most applicable method to use in gathering data. The survey method is defined as a research method for collecting data from a predefined group of respondents to gain information. The researchers used convenience sampling because the respondents were chosen based on their availability. Based on the results of the study, fear of speaking in front of many people, lack of confidence, and being lazy to do the preparation can affect the students’ performance when reporting in the class. However, class presentation and communication skills can help the students enhance their confidence and increase the level of their communication skills. During the class presentation, students build their thinking and analyze their studies to boost their confidence. Communication skills will help the students share ideas and have good leadership skills. Using these two customers may help the students to make techniques that they may use for reporting. The researchers recommended the students learn how to manage their time and give importance to the tasks that will be given to them. Be confident when speaking as they express their feelings and their understanding to their classmates. The researchers also suggested increasing the student talking time to allow the students to enhance their ability and boost their self-confidence when reporting in class. Giving topics and activities such as debate, journalism, and broadcasting may stimulate the interest of the students and help the students to increase their linguistic competence.
Keywords: enhancement, reporting skills, performance tasks, communication skills